Peningkatan Daya Saing Internasional Krusial dalam Exit Strategi dari Program IMF - Sri Adiningsih (Unisia, 2003)
Based on Indonesian economy development lately, it could be said that fundamental macro economy stronger than before. This condition indicates that could be a basic for Indonesia to exit from IMF program. Because of this, if this policy can be reached and the microeconomics can be structured, the IMF exit strategy will not shock Indonesian economy. So it is important to build competitive advantage especially how to increase export, infestationand decrease imported goods. For long term, this policy prepares the opportunity to create a vocation, so the unemployment problems can be solved.